Comparison of Quality of Life and Psychological Well-being of Patients with Cardiovascular Disease and Cancer as well as Healthy People - Farzaneh Afsharnia; Mansor Bayrami (Hamadan University of Medical Sciences, 2018)
Background and Objectives: Quality of life and psychological well-being are one of the issues that can play an important role in the development of diseases and their treatment. This study was conducted with the aim of comparing the quality of life and psychological well-being of patients with cardiovascular disease and cancer as well as healthy people. Materials and Methods: The study is a causal-comparative design. The study population included all patients with cardiovascular disease and cancer at Avicenna Clinic in Tabriz in 2016, and the samples were selected by purposive sampling. The total sample included 150 participants, 100 of whom were selected from the clinical population and 50 of whom were selected from healthy individuals. The data were collected by two questionnaires of quality of life and psychological wellbeing. The data were analyzed by descriptive statistics (mean and standard deviation) and multivariate analysis of variance (MANOVA). Results: The quality of life of healthy people was at a higher level and there were no differences between patients with cardiovascular disease and cancer. Psychological well-being was at a higher level in healthy people than in patients with cardiovascular disease and cancer. Also, this variable was higher in patients with cardiovascular disease than in patients with cancer. Conclusion: Patients with cardiovascular disease and cancer have lower levels of quality of life and psychological well-being than healthy people.